Morphological analysis of the male reproductive accessory glands of the bat Artibeus lituratus (Phyllostomidae: Chiroptera) - Santos, Renata T. S.; Pires, Laís R. M.; Albernaz, Edna S. S.; Andrade, Cleber S.; Santiago, Cornélio S.; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastião R. [UNESP]; Beguelini, Mateus R. (Wiley, 2018)
Bats are distributed worldwide from tropical to temperate regions. Despite their wide geographical radiation and advances in studies using evolutionary approaches, aspects related to the reproduction of these animals remain poorly explored, especially those related to the male reproductive accessory glands (RAGs). Thus, the aim of this study was to analyze the morphophysiology of the male RAGs in the bat Artibeus lituratus. The RAGs in A. lituratus are composed of a compact intra-abdominal glandular complex, consisting of the prostate with two prostatic regions (ventral and dorsal), plus Littre glands and a pair of extra-abdominal bulbourethral glands. The ventral region of the prostate has an epithelium with variable morphology, due to its holocrine type of secretion. In contrast, the dorsal region has a typical cubic-to-columnar pseudostratified epithelium. Both regions contain two cell types, basal and secretory cells. Similar to the epithelial morphology, the secretion also varies, with the ventral region containing numerous PAS-positive globular vesicles, whereas the dorsal region has a more fluid, hyaline and PAS-negative secretion. Littre glands are dispersed in the connective tissue of the urethra, while the bulbourethral glands are located in the penile root, both glands with cubic-to-columnar pseudostratified epithelium and globular PAS-positive secretion. The results demonstrate that the RAGs of A. lituratus are composed of two prostatic regions, ventral and dorsal, and urethral and bulbourethral glands, with no seminal vesicles. Each prostatic region has unique and distinctive characteristics, with the ventral region presenting an exclusive holocrine nature and the dorsal region having similarities to the ventral prostate of rodents.
Keywords: bulbourethral gland; Littre glands; prostate; reproduction